Fitting state–space models to seal populations with scarce data. (16th November 2014) - Øigård, Tor Arne; Skaug, Hans J.
Abstract: We estimate temporal variation in fecundity, the reproduction rate, for Barents Sea and Greenland Sea harp seals using a state–space approach. A stochastic process model for fecundity is integrated with an age-structured population dynamics model and fit to available data for these two harp seal populations. Owing to scarceness of data, it is necessary to "borrow strength" from the Northwest Atlantic harp seal population in form of prior distributions on autocorrelation and variance in fecundity. Comparison is made to a simpler deterministic population dynamics model. The state–space model is more flexible and is able to account for the variations in the data. For Barents Sea harp seals, the state–space model gives a higher estimate of current population size but also a much higher associated uncertainty. In the Greenland Sea, the differences between the stochastic and deterministic models are much smaller.